The Effect Of Marketing and Market Knowledge In Achieving Sustainable Marketing Performance : An Applied Study In A Sample Of Iraqi Industrial Companies - Ahmed Kadem Abed AL Aboudy; Nadia Kazem Awad Hussein; Majid Fahem Jaafar (International Journal of Economics, Management and Accounting, 2024)
The current research collected and studied the three variables that the previous researches are not gathered together.The research aims to find out the effect of marketing and market knowledge in achieving sustainable marketing performance through stated and procedural knowledge represented by marketing thinking to help reach marketing goals by relying on marketing data and information obtained from the market to provide new capabilities and distinct competitive capabilities. The research was applied to a sample of individuals working in Iraqi industrial companies, including the managers, as well as heads of departments and directors of divisions and units.. The focus was on the General Company for Batteries Manufacturing with its two factories, namely the Babel Factory (1) and the Babel Factory (2). A questionnaire was designed to be consistent with purposes of research and its hypothesis. Questionnaires were distributed (122), and (120) Questionnaires were retrieved from them for statistical analysis, i.e. with rate of (98.3%). The research touched a set of deductions, the most significant of which was that marketing and marketing knowledge helps in achieving sustainable marketing performance by carrying out distinct activities, searching for information and knowledge related to customers and competitors, and surveying the market in the long term, it has become an important element in achieving success for contemporary organizations. The research recommends the need to increase companies' interest in market knowledge, and to take the necessary measures to enable them to benefit from this knowledge in creating marketing human capital capable of raising the efficiency of sustainable marketing performance of these companies in short and long term.